2000
DOI: 10.1021/jp000306s
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman Characterization of Excitonically Coupled meso,meso-Linked Porphyrin Arrays

Abstract: Resonance Raman (RR) spectra are reported for dimeric, trimeric, and tetrameric porphyrin arrays in which the porphyrins are directly linked at the meso position. The RR spectra of two monomeric building blocks of the arrays are also examined. The close proximity and orthogonal orientation of adjacent porphyrins in the arrays result in exceptionally strong excitonic interactions along the axis defined by the meso,meso-linkage-(s) and negligible interactions along the orthogonal axis. The coupling scheme breaks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 50 publications
(68 reference statements)
1
24
0
Order By: Relevance
“…Bhuiyan et al 20 examined the RR scattering characteristics of dimeric, trimeric and tetrameric meso,meso-linked porphyrin arrays and reported novel RR scattering characteristics not previously observed for metalloporphyrins. In particular they noted the intensity enhancement of anomalously polarized bands with B-state excitation and attributed the unusual enhancement to uniaxial excitonic interactions, which contribute to symmetry lowering in the excited states.…”
Section: Mechanism Of Enhancementmentioning
confidence: 96%
See 2 more Smart Citations
“…Bhuiyan et al 20 examined the RR scattering characteristics of dimeric, trimeric and tetrameric meso,meso-linked porphyrin arrays and reported novel RR scattering characteristics not previously observed for metalloporphyrins. In particular they noted the intensity enhancement of anomalously polarized bands with B-state excitation and attributed the unusual enhancement to uniaxial excitonic interactions, which contribute to symmetry lowering in the excited states.…”
Section: Mechanism Of Enhancementmentioning
confidence: 96%
“…The symmetry lowering promotes novel Frank-Condon and vibronic scattering mechanism in the B state(s) of the arrays. 20 In the present study the unusual enhancement is observed at 632.8 nm approximately 200 nm red shifted from the B state, so the mechanism for enhancement would be different to that reported by Bhuiyan et al 20 Nevertheless, the unusual RR enhancement observed by Bhuiyan et al and the SCD results reported by Goldbeck et al 22 on dimeric and tetrameric haems do set a precedence to explain the unusual enhancement observed in Hb encapsulated within single red blood cells with 632.8 nm excitation. Further experiments are required to validate the excitation coupling hypothesis as a mechanism to explain the unusual enhancement observed at 632.8 nm, which is the subject of continuing studies by our group.…”
Section: Mechanism Of Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregated enhanced Raman scattering (AERS) has been proposed to explain the anomalous enhancement observed in N-protonated porphyrins [4] and cyanine dyes absorbed onto surfaces [5]. Covalently linked porphyrin architectures including meso-meso-linked arrays of copper(II) [6,7] and zinc(II) [8] exhibit strong excitonic interactions showing a distinct splitting of the Soret band and unusual Raman scattering patterns. The propionate linkage between porphyrin units in malaria pigment (hemozoin) may also enable excitonic coupling, although to a lesser extent than in meso-meso-linked arrays.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Semisynthetic products, which were derived from chlorophyll a, and which are also capable of selfassembly, were recently described. [15] If practical uses are envisaged, our synthetic strategies, which are high yielding and use cheap starting materials, are superior as the starting material, copper 10,20-bis-(3,5-di-tert-butylphenyl) porphyrin [16] is easily available in multigram quantities.…”
mentioning
confidence: 99%